2022
DOI: 10.56499/jppres22.1342_10.3.551
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and antioxidant capacity of the aqueous extracts of Malva sylvestris L. and Malva pseudolavatera Webb & Berthel.

Abstract: Context: Malva spp. have been widely used in the world as traditional remedies. In Ecuadorian markers Malva sylvestris and Malva pseudolavatera are the species most commercialized. However, the scientific information about M. pseudolavatera is little. Aims: To determine the chemical composition and antioxidant capacity of the aqueous extracts of the leaves of both species. Methods: Aqueous extracts were partitioned with butanol and the fractions obtained were analyzed by GC/MS. Total extracts were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Malva sylvestris and Malva pseudolavatera species are the main ones sold in Ecuadorian markets. Antioxidant activity measurements by DPPH and ABTS have shown that the aqueous extract of M. sylvestris (IC 50 DPPH = 78.14 µg/mL; IC 50 ABTS = 166.79 µg/mL) was the most antioxidant extract, probably due to the presence of polyols [48]. These results corroborate how important it is to select the appropriate extraction technique as well as the solvent, as they have a direct influence on the bioactive compounds to be obtained.…”
Section: Discussionmentioning
confidence: 55%
“…Malva sylvestris and Malva pseudolavatera species are the main ones sold in Ecuadorian markets. Antioxidant activity measurements by DPPH and ABTS have shown that the aqueous extract of M. sylvestris (IC 50 DPPH = 78.14 µg/mL; IC 50 ABTS = 166.79 µg/mL) was the most antioxidant extract, probably due to the presence of polyols [48]. These results corroborate how important it is to select the appropriate extraction technique as well as the solvent, as they have a direct influence on the bioactive compounds to be obtained.…”
Section: Discussionmentioning
confidence: 55%
“…Trolox was used as a reference compound in a concentration range of 0.0312-0.5 mM. Results were expressed as mmol Trolox equivalents/g (TEAC: Trolox equivalent antioxidant capacity) (Ramos-Escudero et al, 2012;Sarmiento et al, 2022).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The antioxidant activity was expressed as the value of the 50% inhibitory concentration (IC50). The DPPH radical solution was prepared at a concentration of 100 mM in 80%( v /v) methanol (Ramos-Escudero et al, 2012;Sarmiento et al, 2022).…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation